Laser Diode Enhances Autologous Cartilage Graft's Expansibility - R.Mohammed, Ihsan, F.; Al-Mustawfi, Nuha S.; Al- Iedan, Mohammed S. (AL-Kindy College Medical Journal, 2016)
Background: Cartilage forms most of the temporary skeleton of the embryo and provides a model in which most bones developObjective: Using laser therapy to enhance autologous cartilage grafts expansibility and to analyze whether this "enhancement" results in reduced rates of cartilage resorption and greater preservation of normal architectural features compared with "unenhanced" grafts. Type of the study: Cross sectional study.Methods: 24 New Zealand rabbits were divided into two groups (control and treated with 904nm, 10mW diode laser). Auricular cartilage segments measuring 1 cm2 were harvested from both ears of each rabbit, and were implanted in to the subcutaneous region of the left flank. 3 rabbits from each group were anaesthetized at 3, 6, 9 and 12 weeks post operation, implanted cartilages were then peeled. Gross and microscopic examinations were performed to assess size, structural integrity, and architectural features, with comparisons performed between each of the conditions. The results were assessed using T – test. Results: Grafts of control group were softer, more pliable when compared with grafts treated with laser irradiation. The rate of healing, and the quality of the cartilage is more enhanced in the treated group. The mean areas of the harvested cartilage grafts treated with laser therapy were 1.17 cm2 , 1.34 cm2, 1,64 cm2 and 1.76 cm2 respectively, while the corresponding value for the untreated specimens was 0.95 cm2, 0,99 cm2, 1.05 cm2 and 1.08 cm2. The percentage of decrease in size was 14% for the untreated specimens and 0% for the specimens treated with laser therapy for all cases. Conclusions: Our findings demonstrated significant improvements in graft quality using laser therapy. These findings may justify changes in how cartilage grafts are prepared and delivered for facial augmentation procedures to reduce graft resorption and maintain the structural integrity of the cartilage.